EFEK DIURETIK SEDUHAN DAUN TEH HIJAU (Camellia sinensis L.) PADA MENCIT JANTAN GALUR SWISS - Agustina Susilowati; Nanda Syta Nur’aini (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2022)
The use of diuretics is needed in all circumstances requiring increased water expenditure, one of which is hypertension. Green tea has has flavonoids and alkaloids and has proven efficacy as a diuretic. This study aims to find the diuretic effect of steeping green tea leaves on Swiss male mice. This study used 25 male swiss mice which were divided into five groups, namely Group I as negative control given 1% CMC Na solution, group II as positive control was given furosemide suspension dose 5.2 mg / KgBW, and groups III, IV and V given the steeping of green tea leaves with a powder weight of 2g, 4g and 6g in 200ml of hot water. Before being given the treatment, each group was given 0.4 ml warm water. Testing of the diuretic effect comparison is done by looking at the volume of urine produced every 1 hour for 6 hours. The results of the urine volume of mice were analyzed with SPSS 24 with a confidence level of 95%.The results of phytochemical screening show that the steeping of green tea leaves contains alkaloids, flavonoids, saponin and tannins. The average cumulative volume of urine for group I was 0.376 mL, group II was 1.119 mL, group III was 0.431 mL, group IV was 0.661 mL and group V was 0.725 mL. Steeping green tea leaves 4g and 6g (p≥ 0,05) can have a diuretic effect in male Swiss mice.